2016
DOI: 10.1248/bpb.b16-00087
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Antigen Combined with αβ-ATP as a Vaccine Adjuvant Enhances Antigen-Specific Antibody Production <i>via</i> Dendritic Cell Activation

Abstract: Adjuvants are required to enhance antigen-specific immune responses by vaccines. Extracellular ATP serves as a danger signal to alert the immune system of tissue damage by acting on P2X and P2Y receptors and triggers the activation of dendritic cells (DCs). Here we investigated the in vivo adjuvant efficacy of α,β-methylene-ATP (αβ-ATP), a non-hydrolysable form of ATP. We found that intradermal injection of ovalbumin (OVA), as a model antigen, combined with αβ-ATP, as the adjuvant, enhanced OVA-specific immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our understanding of the immunological characteristics of P2RY6 microenvironment makes us confident to infer that LUAD may affect tumor immunity and thus affect the prognosis of LUAD patients. Some genes of the same family with P2RY6 have developed corresponding immunotherapy [ 50 ]. Inspired by this, we think that P2RY6 may have a good prospect in the immune regulation of tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the immunological characteristics of P2RY6 microenvironment makes us confident to infer that LUAD may affect tumor immunity and thus affect the prognosis of LUAD patients. Some genes of the same family with P2RY6 have developed corresponding immunotherapy [ 50 ]. Inspired by this, we think that P2RY6 may have a good prospect in the immune regulation of tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the immunological characteristics of P2RY6 microenvironment makes us con dent to infer that LUAD may affect tumor immunity and thus affect the prognosis of LUAD patients. Some genes of the same family with P2RY6 have developed corresponding immunotherapy [44] . Inspired by this, we think that P2RY6 may have a good prospect in the immune regulation of tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…MF59 induces ATP release from cells at the injection site . Indeed, non‐hydrolysable ATP can act as a vaccine adjuvant, resulting in enhancement of antigen‐specific antibody responses . ATP may also activate Tregs and enhance their suppressive ability , although other studies showed that ATP can inhibit the suppressive ability and stability of Tregs .…”
Section: Discussionmentioning
confidence: 99%